Penguatan Layanan Bimbingan dan Konseling di Era Multikultural melaui Integrasi Kearifan Lokal - Rusmanita Amalia Sari; Budiyanto Budiyanto; Evi Winingsih (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This article critically examines the strengthening of guidance and counseling services through the integration of local wisdom in multicultural contexts, positioning it as a pathway for decolonizing counseling knowledge and practice in Indonesia. Increasing cultural diversity demands context-sensitive approaches, yet current practices remain largely influenced by Western models that may not align with Indonesia’s sociocultural realities. Therefore, this study explores how integrating local wisdom can enhance guidance and counseling services within a decolonization framework. The study uses a systematic literature review by analyzing various scientific publications related to decolonization, multicultural counseling, and the use of local cultural values in education and counseling. The findings show that integrating local wisdom into counseling practices can improve cultural relevance, encourage relational and collective values, and support the development of culturally responsive interventions. In addition, the results indicate that decolonizing counseling practices allows a shift from general, universal approaches to models that are more context-based and rooted in indigenous perspectives. In conclusion, integrating local wisdom within a decolonization framework can be an effective strategy to strengthen multicultural guidance and counseling services in Indonesia, making them more relevant, effective, and responsive to students’ needs. The findings indicate that embedding local wisdom into GC practice does not merely function as cultural enrichment, but substantially strengthens students’ cultural and spiritual identity, while enhancing the effectiveness, empathy, and contextual relevance of services in pluralistic educational environments. The study concludes that integrating local wisdom into guidance and counseling services is a crucial step in the decolonization of counseling science in Indonesia and an essential response to the challenges posed by globalization and cultural heterogeneity. Such integration opens opportunities to develop counseling models that are not only culturally adapted, but culturally rooted-reflecting Indonesia’s epistemic identity and lived realities.